New possibilities of excessive postoperative scarring prophylaxis by glaucoma surgery - A. Yu. Slonimskiy; I. B. Alekseyev; S. S. Dolgiy (Oftalʹmologiâ, 2014)
Purpose: to access the possibilities of new biodegradable drainage implant Glautex in the original method of glaucoma surgical treatment.Methods: 152 patients (158 eyes) have had a penetrating and nonpenetrating antiglaucoma surgical treatment with the use of Glautex. Patients were divided in 3 groups: 1st group — 90 patients (93 eyes), where valve trabeculectomy with the use of biodegrad- able drainage Glautex has been performed. 2nd group — 33 patients (35 eyes) with refractory glaucoma (previously operated glau- coma, postkeratoplasty, neovascular glaucoma etc.) with the same type of antiglaucoma surgery. 3rd group — 29 patients (30 eyes) with deep non-penetrating sclerectomy with the use of Glautex.Results: Stable IOP has been obtained in all cases within 6 to 12 months’ time. Complete biodegradation of the implant took place in 4-5 months, which was confirmed by ultrasound biomicroscopy. We have obtained no cases of inflammation in postoperative period. No cases of blebitis and cystoid blebs have been noted. the choroidal detachment, requiring surgical treatment was noted on 7 eyes (7.5%) in the 1st group; in the 2nd group — on 3 eyes (8.6%). the 3rd group (nonpenetrating glaucoma surgery) had 2 cases of flat choroidal detachment, which have successfully cured after medical nonsurgical treatment.Conclusion: Use of the new biodegradable drainage implant Glautex provides stable decrease of IOP due to prevention of sclero- conjunctival and sclero-scleral adhesions. Glautex may be used in all cases of glaucoma surgery (penetrating and nonpenetrating) with the scleral flap formation. the proposed new method is applicable for all types of glaucoma.